Changes in predator exposure, but not in diet, induce phenotypic plasticity in scorpion venom. Issue 1863 (27th September 2017) - Gangur, Alex N.; Smout, Michael; Liddell, Michael J.; Seymour, Jamie E.; Wilson, David; Northfield, Tobin D.
Abstract : Animals embedded between trophic levels must simultaneously balance pressures to deter predators and acquire resources. Venomous animals may use venom toxins to mediate both pressures, and thus changes in this balance may alter the composition of venoms. Basic theory suggests that greater exposure to a predator should induce a larger proportion of defensive venom components relative to offensive venom components, while increases in arms races with prey will elicit the reverse. Alternatively, reducing the need for venom expenditure for food acquisition, for example because of an increase in scavenging, may reduce the production of offensive venom components. Here, we investigated changes in scorpion venom composition using a mesocosm experiment where we manipulated scorpions' exposure to a surrogate vertebrate predator and live and dead prey. After six weeks, scorpions exposed to surrogate predators exhibited significantly different venom chemistry compared with naive scorpions. This change included a relative increase in some compounds toxic to vertebrate cells and a relative decrease in some compounds effective against their invertebrate prey. Our findings provide, to our knowledge, the first evidence for adaptive plasticity in venom composition. These changes in venom composition may increase the stability of food webs involving venomous animals.